Use of clinoptilolite zeolite on selected soil chemical properties, dry matter production, nutrients uptake and use efficiency of Zea mays cultivated on an acid soil - Hasbullah, Nor Aainaa; Ahmed, Osumanu Haruna; Kasim, Susilawati; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2014)
In acid soils of the humid tropics, Phosphorus (P) deficiency due to its fixation by Al and Fe is common. It is therefore important to ensure adequate supply of P for optimum crop production. The use of zeolite on acid soils could fix Al and Fe and thus, rendering P readily available for crop use. The objective of the study was to determine the effects of including clinoptilolite zeolite in Zea mays cultivation on an acid soil on selected soil chemical properties, dry matter production, nutrient uptake and use efficiency of Zea mays. Triple Super Phosphate (TSP), urea and Muriate of Potash (MOP) were used in this study. Twenty five percent of the recommended N, P and K fertilizers for Zea mays were replaced with Clinoptilolite zeolite. Standard procedures were used to determine soil pH, exchangeable ammonium, available nitrate, available phosphorus, exchangeable aluminium, iron, cations and organic matter before and after planting. The plants were harvested at tasselling stage and measured for dry matter production, nutrients uptake and use efficiency. The effect of zeolite application with 75% of fertilization (T2) and 100% fertilization (T1) on soil chemical properties were statistically similar. Similar observation was made on dry matter production, nutrients concentration, nutrients uptake and nutrients use efficiency. The findings reported in this paper indicate that Clinoptilolite zeolite could be used to reduce the use of N, P and K fertilizers use of Zea mays on acid soils. At least three cropping cycles are recommended to confirm the findings of this study. It is also essential to estimate the economic benefits of including zeolite in Zea mays cultivation. These aspects are being investigated in on-going field trial.